2013
DOI: 10.3390/molecules181011683
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Amide Bond Conformers for a Novel Heterocyclic Template of N-acylhydrazone Derivatives

Abstract: Herein we describe NMR experiments and structural modifications of 4-methyl-2-phenylpyrimidine-N-acylhydrazone compounds (aryl-NAH) in order to discover if duplication of some signals in their 1 H-and 13 C-NMR spectra was related to a mixture of imine double bond stereoisomers (E/Z) or CO-NH bond conformers (syn and anti-periplanar). NMR data from NOEdiff, 2D-NOESY and 1 H-NMR spectra at different temperatures, and also the synthesis of isopropylidene hydrazone revealed the nature of duplicated signals of a 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 25 publications
6
68
0
Order By: Relevance
“…In a study involving compounds 1f and 1 g, the 1 H-NMR spectra obtained in DMSO- d 6 at 90°C showed that the two species were in rapid equilibrium (Figures S12–S13 and S15–S16 in File S1). Interestingly, a complete coalescence of the signals was achieved at 90°C, and the reversibility of the changes was verified, indicating the presence of conformational isomers [22], [23]. Indeed, a Monte Carlo conformational search performed on derivative 1 g followed by energy calculations of the selected conformers according to the Hartree-Fock 3–21G method indicated a slight difference in energy (ΔE =  −19.83 kJ.mol -1 ) between the synperiplanar and antiperiplanar conformers in the favor of the former (Figure 3).…”
Section: Resultsmentioning
confidence: 87%
“…In a study involving compounds 1f and 1 g, the 1 H-NMR spectra obtained in DMSO- d 6 at 90°C showed that the two species were in rapid equilibrium (Figures S12–S13 and S15–S16 in File S1). Interestingly, a complete coalescence of the signals was achieved at 90°C, and the reversibility of the changes was verified, indicating the presence of conformational isomers [22], [23]. Indeed, a Monte Carlo conformational search performed on derivative 1 g followed by energy calculations of the selected conformers according to the Hartree-Fock 3–21G method indicated a slight difference in energy (ΔE =  −19.83 kJ.mol -1 ) between the synperiplanar and antiperiplanar conformers in the favor of the former (Figure 3).…”
Section: Resultsmentioning
confidence: 87%
“…In Figure 3b Index ranges bond (E C=N and Z C=N ), making four possible arrangements in all about the C(O)−NH−N=CH-aryl fragment. [32][33][34][35] While the triazolyl ring is planar in all compounds, none of the compounds is planar overall. The deviation from planarity is relatively small for the 2H-1,2,3-triazolyl compounds, 2a, 2b and 3, as shown by the angles between the aryl rings in Table 3, and very much larger for 1a and 1b (see Figure 4).…”
Section: Molecular Conformationsmentioning
confidence: 99%
“…Different practical and computational experiments reported in the literature displayed the existence of the formed N ‐acylhydrazones in the sterically less hindered geometric E isomer and the duplication of signals was attributed to the presence of cis and trans conformers on CO–NH. [ 59–63 ] Based on the reported findings, the duplication of signals in the obtained nuclear magnetic resonance (NMR) spectra of 9a – n and 10a , b was rationalized to the presence of a mixture of cis and trans conformers C and D in ratios between 2:1 and 3:1 in the used NMR solvent (Figure 4; for further details see Section 4 and the Supporting Information Data).…”
Section: Resultsmentioning
confidence: 91%